Evaluasi Penerapan Sistem Pembukuan Manual dalam Penyusunan Laporan Keuangan pada PT Javindo Utama Tahun 2022-2024 - Viera Pramestya Makuta; Saridawati Saridawati (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Manual bookkeeping system Manual bookkeeping is a system of recording financial transactions that is carried out conventionally using ledgers, journals, and worksheets without the help of accounting software. Manual bookkeeping has advantages in terms of cost affordability and ease of implementation for small businesses. However, the main weakness of this system is its susceptibility to recording errors and delays in preparing financial reports. PT Javindo is a medium- scale company in the construction sector that still uses a manual bookkeeping system. This has had an impact on the results of financial reports that are less credible and prone to misrepresentation and do not comply with financial accounting standards in Indonesia. The evaluation results concluded that there were many weaknesses in the implementation of the manual bookkeeping system, so it is better for PT Javindo to revolutionize the system and implement accounting system-based recording.